Differences in EEG Oscillations during Vasoactive Stress Reactions in Extroverts and Introverts - A M Kustubayeva; Gerald Matthews (Peoples' Friendship University of Russia (RUDN University), 2012)
Hyperventilation (HV) and breath-holding (BH) are informative psychophysiological tests resulting in rapidly changing cerebral blood flow. The aim of our research was to determine differential EEG spectra of introverts/extroverts with induced HV and BH. Introverts revealed more intensive EEG reaction during HV, which was specifically shown by increased theta and gamma activity in all cortical areas.